2022
DOI: 10.1002/jbt.23198
|View full text |Cite
|
Sign up to set email alerts
|

miR‐125a‐3p aggravates ox‐LDL‐induced HUVEC injury through BAMBI

Abstract: Atherosclerosis (AS) is a chronic inflammatory disease characterized by the formation of atherosclerotic plaque in the intima of arteries. Among the known regulators of atherosclerosis, microRNAs (miRNAs) have been reported to play critical roles in lipoprotein homeostasis and plaque formation. But the roles of microRNA‐125a‐3p (miR‐125a‐3p) in the pathogenesis of AS remain unknown. Human umbilical vein endothelial cells (HUVECs) were treated with oxidized low‐density lipoprotein (ox‐LDL) to construct the vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This network was established to investigate the mechanism of YTHDC1. Results showed that miR-125a-3p involved in regulating cell proliferation and apoptosis [ [51] , [52] , [53] ]. Our Result showed that miR-125-3p may contribute to PAECs dysfunction and pulmonary remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…This network was established to investigate the mechanism of YTHDC1. Results showed that miR-125a-3p involved in regulating cell proliferation and apoptosis [ [51] , [52] , [53] ]. Our Result showed that miR-125-3p may contribute to PAECs dysfunction and pulmonary remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-125a-3p may be closely related to AS pathogenesis. Xia and Zeng found that miR-125a-3p aggravates Ox-LDL-induced HUVEC injury through BAMBI [ 31 ]. Hu et al confirmed that miR-125a-3p can effectively inhibit the function of VSMCs and the occurrence of vascular stenosis by targeting MAPK1 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through LncRNA2Target prediction and dual-luciferase reporter assay, we identified lncRNA-Gm5532 as a ceRNA by targeting miR-125a-3p. miR-125a-3p was reported to be involved in the progression of multiple diseases, including atherosclerosis [22] , cataracts [23] , rheumatoid arthritis [24] , papillary thyroid carcinoma [25] , breast cancer [26] , and colorectal cancer [27] . In addition, miR-125a-3p is a potential regulator of bone homeostasis.…”
Section: Discussionmentioning
confidence: 99%